Dose-Response Effects of Acute Aerobic Exercise Intensity on Inhibitory Control in Children With Attention Deficit/Hyperactivity Disorder - Tsai, Yu-Jung; Hsieh, Shu-Shih; Huang, Chung-Ju; Hung, Tsung-Min (Frontiers in Human Neuroscience, 2021)
The present study aimed to examine whether the effect of acute aerobic exercise on inhibitory control of children with ADHD is moderated by exercise intensity. Using a within-subjects design, 25 children with ADHD completed a flanker task with concurrent collection of electroencephalography (EEG) data after three different intensities of treadmill running. The results showed that low- and moderate-intensity exercise resulted in shorter reaction times relative to vigorous-intensity exercise during the incompatible condition of the flanker task regardless of task congruency. A P3 congruency effect was observed following low- and vigorous-intensity exercise but not after moderate-intensity exercise. The mean alpha power, a measure of cortical arousal, increased following low- and moderate-intensity exercise, but decreased following vigorous exercise intensity. In addition, the change in arousal level after moderate-intensity exercise was negatively correlated with reaction time during incompatible flanker tasks. The current findings suggest that children with ADHD have better inhibitory control following both low- and moderate-intensity exercise relative to vigorous aerobic exercise, which could be characterized by an optimal state of cortical arousal.